Garlic; micropropagation; in vitro culture. - Brenes-Madriz, Jaime A. (2014)
The cultivation of garlic in Costa Rica tends to disappear, because this vegetable imports from China and Taiwan and loss of quality and seed vigor, which caused a reduction of planting area in the country. For the research presented in this article garlic grown in the area of Llano Grande, Carthage, belonging to small farmers who sow seed inherited from generation to generation were used. Four disinfection with sodium hypochlorite at different concentrations and exposure times were evaluated, plus four culture media M & S (1962), with different growth regulators. Most survival for establishing in vitro was obtained by washing the cloves with soap and water and then passing them to a solution of Zetaran® and Agri-mycim® 5 g / l each for 45 minutes. A second disinfection with sodium hypochlorite was then performed at 3.5% w / v for 20 minutes in a laminar flow chamber and three washes with sterile double distilled water were conducted. The culture medium provided the best results was Murashige and Skoog (1962) supplemented with 1 mg / L 2-isopentenyladenine (2iP) and 2.5 mg / L indoleacetic acid (IAA). The survival rate of explants hovers around 28.7% and an average of 1.6 shoots per explant was obtained, which is considered a very low rate of sprouting. Título: Establishment of an in vitro cultivation of garlic (Allium sativum) protocol in Costa Rica.